An incident of water and soil gushing in a metro tunnel due to high water pressure in sandy silt. (March 2021) - Zhang, Dong-Mei; Xie, Xiao-Chuang; Zhou, Ming-Liang; Huang, Zhong-Kai; Zhang, Dong-Ming
Highlights: Investigated the incident, the asscocited damages, and the remedial measures. The high water pressure in sandy silt caused the water and soil penetration. The monitoring program played a significant role in controlling the incident. The remedial measures effectively improved the stability of the damaged tunnel. Provides practical guidance for mitigating the risk of water and soil gushing. Abstract: A connecting passage of the Metro Line 18 in Shanghai was under construction in a sand layer featuring high fine content and a high level of confined water head. During the tunnel construction, an incident of water and soil gushing through the freezing holes resulted in large settlement and damage to the tunnel linings. The remedial measures were then carried out to prevent the incident and to strengthen the damaged tunnel linings. This paper analyzes the reasons for the water and soil gushing, the damage to the tunnels, and the effect of the remedial measures. The main reason for the incident was water and sand penetration through the gap between the freezing pipes and the borehole orifice pipes due to the high water pressure outside the tunnels. The monitoring results indicate that the grouting and the lining reinforcement with reinforced steel ring effectively improved the stability of the tunnel structures. This case study provides practical experience and guidance for similar tunnelling projects in the future to mitigate the risk of water and soil gushing.